Role of CXCL5 in Regulating Chemotaxis of Innate and Adaptive Leukocytes in Infected Lungs Upon Pulmonary Influenza Infection - Guo, Lei; Li, Nan; Yang, Zening; Li, Heng; Zheng, Huiwen; Yang, Jinxi; Chen, Yanli; Zhao, Xin; Mei, Junjie; Shi, Haijing; Worthen, G. Scott; Liu, Longding (Frontiers in Immunology, 2021)
Respirovirus such as influenza virus infection induces pulmonary anti-viral immune response, orchestration of innate and adaptive immunity restrain viral infection, otherwise causes severe diseases such as pneumonia. Chemokines regulate leukocyte recruitment to the inflammation site. One chemokine CXCL5, plays a scavenging role to regulate pulmonary host defense against bacterial infection, but its role in pulmonary influenza virus infection is underdetermined. Here, using an influenza (H1N1) infected CXCL5-/- mouse model, we found that CXCL5 not only responds to neutrophil infiltration into infected lungs at the innate immunity stage, but also affects B lymphocyte accumulation in the lungs by regulating the expression of the B cell chemokine CXCL13. Inhibition of CXCL5-CXCR2 axis markedly induces CXCL13 expression in CD64+CD44hiCD274hi macrophages/monocytes in infected lungs, and in vitro administration of CXCL5 to CD64+ alveolar macrophages suppresses CXCL13 expression via the CXCL5-CXCR2 axis upon influenza challenge. CXCL5 deficiency leads to increased B lymphocyte accumulation in infected lungs, contributing to an enhanced B cell immune response and facilitating induced bronchus-associated lymphoid tissue formation in the infected lungs during the late infection and recovery stages. These data highlight multiple regulatory roles of CXCL5 in leukocyte chemotaxis during pulmonary influenza infection.